Beckman R A Cart (RAC) (1987)
Although otherwise unidentified, this item is very likely a metabolism analysis cart that measures oxygen and carbon dioxide respiration.
Keywords: Respiration; Oxygen--Measurement; Oxygen--Analysis; Oxygen--Metabolism; Beckman Instruments, Inc.; Carbon dioxide